Assessment of Radiation Dosage to the Hippocampi during Treatment of Multiple Brain Metastases Using Gamma Knife Therapy - Maciej Laskowski; Bartłomiej Błaszczyk; Marcin Setlak; Maciej Kuca; Arkadiusz Lech; Kamil Kłos; Adam Rudnik (Medicina, 2024)
Background and Objectives: Brain metastases (BMs) pose significant clinical challenges in systemic cancer patients. They often cause symptoms related to brain compression and are typically managed with multimodal therapies, such as surgery, chemotherapy, whole brain radiotherapy (WBRT), and stereotactic radiosurgery (SRS). With modern oncology treatments prolonging survival, concerns about the neurocognitive side effects of BM treatments are growing. WBRT, though widely used for multiple BMs, has recognized neurocognitive toxicity. SRS, particularly Gamma Knife (GK) therapy, offers a minimally invasive alternative with fewer side effects, suitable for patients with a quantifiable number of metastases and better prognoses. Materials and Methods: A retrospective analysis was conducted on 94 patients with multiple BMs treated exclusively with GK at an academic medical center. Patients with prior WBRT were excluded. This study focused on the mean radiation dose received by the hippocampal area, estimated according to the ‘Hippocampal Contouring: A Contouring Atlas for RTOG 0933’ guidelines. Results: The precision of GK equipment results in mean doses of radiation that are lower than those suggested by RTOG 0933 and observed in other studies. This precision may help mitigate cognitive dysfunction and other side effects of hippocampal irradiation. Conclusions: GK therapy facilitates the administration of smaller, safer radiation doses to the hippocampi, which is advantageous even for lesions in the temporal lobe. It is feasible to treat multiple metastases, including cases with more than 10, but it is typically reserved for patients with fewer metastases, with an average of 3 in this study. This underlines GK’s potential for reducing adverse effects while managing BMs effectively.